Agency Conflicts in Closed-End Funds: The Case of Rights Offerings - Khorana, Ajay; Wahal, Sunil; Zenner, Marc (Journal of Financial and Quantitative Analysis, 2002)
We study 120 rights offerings by closed-end funds from 1988-1998. On average, rights offerings are announced when funds trade at a premium. This premium turns into a discount over the course of the offering. The premium decline is more severe when increases in the investment advisor's compensation are larger and when the fund uses affiliated brokerdealers to solicit subscriptions to the offer. A clinical analysis shows that rights offerings allow investment advisors to sidestep fee rebates and increase pecuniary benefits to affiliated entities. Overall, our results suggest the presence of significant conflicts of interest in rights offerings by closed-end funds.